2013
DOI: 10.3758/s13421-013-0367-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the cognitive reflection test measure cognitive reflection? A mathematical modeling approach

Abstract: We used a mathematical modelling approach, based on a sample of 2,019 participants, to better understand what the cognitive reflection test (CRT, Frederick, 2005) measures. This test, which is typically completed in less than ten minutes, contains three problems, and aims to measure the ability or disposition to resist reporting the response that first comes to mind.However, since the test contains three mathematical based problems, it is possible that the test only measures mathematical abilities and not cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
209
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(271 citation statements)
references
References 28 publications
23
209
2
3
Order By: Relevance
“…The results confirmed that, in line with several previous studies (e.g., Campitelli & Gerrans, 2014;Cueva et al, 2016;Frederick, 2005;Pennycook et al, 2016;Primi et al, 2016), gender was related to performance on the CRT (i.e., men scored significantly higher than women). However, the gender differences disappeared when numerical skills and math-related anxiety were statistically controlled.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results confirmed that, in line with several previous studies (e.g., Campitelli & Gerrans, 2014;Cueva et al, 2016;Frederick, 2005;Pennycook et al, 2016;Primi et al, 2016), gender was related to performance on the CRT (i.e., men scored significantly higher than women). However, the gender differences disappeared when numerical skills and math-related anxiety were statistically controlled.…”
Section: Discussionsupporting
confidence: 82%
“…However, the gender differences disappeared when numerical skills and math-related anxiety were statistically controlled. Although the CRT is more than just a test of numeracy (e.g., Campitelli & Gerrans, 2014;Liberali et al, 2012), these results suggest that the numerical content of the problems acts as a confounding variable .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The correct response is 5 cents, an answer that is reached by only roughly 30% of university undergraduates, depending on the university (De Neys, Rossi, & Houdé, 2013;Frederick, 2005;Pennycook, Cheyne, Koehler, & Fugelsang, 2016). However, errors are also not random: Almost all who get CRT questions wrong give the intuitive response (Campitelli & Gerrans, 2014;Frederick, 2005;Pennycook, Cheyne, et al, 2016). Moreover, the majority of participants who answer correctly are aware of the incorrect intuitive answer, whereas those who got it wrong naturally failed to consider the correct answer (Mata, Ferreira, & Sherman, 2013;Pennycook, Ross, Koehler, & Fugelsang, 2017).…”
mentioning
confidence: 99%
“…Nonetheless, there is strong evidence that the CRT is not just another numeracy test (Campitelli & Gerrans, 2014;Cokely & Kelley, 2009;Liberali, Reyna, Furlan, Stein, & Pardo, 2011;Toplak, West, & Stanovich, 2011; but see Weller et al, 2013). Under the assumption that one must engage reflective reasoning processes to override a prepotent intuitive response, the willingness or disposition to engage Type 2 processing should be an important determinant of performance.…”
mentioning
confidence: 99%